Magnesium alloy surface high-corrosion-resistance super-hydrophobic composite coating and preparation method thereof

By preparing island anodized layer and needle-shaped electrodeposition superhydrophobic layer on the surface of magnesium alloy, the problem of poor corrosion resistance of magnesium alloy is solved, efficient corrosion protection is achieved, the service life of magnesium alloy is extended, and environmental protection is met and simple equipment requirements.

CN119320972APending Publication Date: 2025-01-17NORTHEASTERN UNIV CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411525075.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Magnesium alloys have poor corrosion resistance and short service life due to chemical activity and loose porosity of the oxide layer, which limits their application in 3C, aerospace, defense and military industry, and energy batteries.

Method used

An anodized layer with an island-like structure and an electrodeposition superhydrophobic layer with a needle-like structure cluster were prepared by combining anodized and electrodeposition method to prepare a high corrosion-resistant superhydrophobic composite coating on the surface of magnesium alloy with a thickness of 20~80μm. Low-surface energy substances and multi-layer micro-nano structures are used to protect the substrate.

Benefits of technology

It significantly delays the corrosion rate of magnesium alloy, enhances the bonding force between the composite coating and the substrate, achieves a long-term anti-corrosion effect, and has environmentally friendly process, short cycle, and does not use toxic substances. It is suitable for different types of magnesium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320972A_ABST
    Figure CN119320972A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium alloy surface high-corrosion-resistance super-hydrophobic composite coating and a preparation method thereof, and belongs to the field of metal material surface treatment and modification. The high-corrosion-resistance super-hydrophobic composite coating on the surface of the magnesium alloy is of a double-layer structure, the inner layer is an anodic oxidation layer of an island-shaped structure, and a magnesium alloy matrix subjected to mechanical polishing and ultrasonic cleaning is directly subjected to anodic oxidation treatment to obtain the high-corrosion-resistance super-hydrophobic composite coating; and the outer layer is a compact super-hydrophobic coating formed by clustering a needle-shaped structure, and is obtained by carrying out electro-deposition treatment on a matrix attached with an anodic oxide layer in a solution containing a low-surface-energy substance. The method is easy to operate and low in cost, the composite super-hydrophobic coating shows better matrix binding force than a single super-hydrophobic coating, the corrosion resistance of the matrix is improved more obviously, and the method has certain application value for prolonging the service life of the magnesium alloy and large-scale development of the super-hydrophobic coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of surface treatment and modification of metal materials, and specifically discloses a highly corrosion-resistant super-hydrophobic composite coating on the surface of a magnesium alloy and a preparation method thereof. Background Art

[0002] Magnesium alloys have the characteristics of high specific strength and specific stiffness, strong resistance to high-energy particle penetration, and excellent shock absorption performance. They show great development prospects in the fields of 3C, aerospace, national defense and military industry, and even biomedicine and energy batteries. But at the same time, the corrosion problem greatly restricts the development and application of Mg alloys. Compared with other metals, magnesium has higher chemical activity and lower standard electrode potential (-2.27V), and the formed oxide layer is loose and porous and difficult to provide effective protection for the matrix, so magnesium is very easy to corrode. This causes problems such as poor corrosion resistance, short service life, and serious material loss of magnesium alloys. This seriously limits the industrial application and economic value of magnesium alloys, so appropriate measures must be taken to slow down the corrosion rate of magnesium alloys.

[0003] Super hydrophobic coating is a practical method to solve the poor corrosion resistance of magnesium and magnesium alloys. In recent years, super hydrophobic surfaces designed based on biomimetic behavior have been proven to have good corrosion protection effects on substrates. This type of coating has an air layer captured by the outermost micro-nano composite structure, a low surface energy layer with an inhibitory effect on charge transfer in the middle, and a dense rough layer connected to the substrate. This "three-barrier" corrosion protection mechanism can prevent ions from further contacting the metal substrate, limit the interaction between metal and corrosive substances (such as water and ions), and reduce the corrosion rate of the alloy. The hydrophobicity of super hydrophobic coating depends on its surface roughness and low surface energy substances, so the construction of super hydrophobic coating is generally to establish a rough micro-nano structure on the alloy surface using different methods, and then to achieve super hydrophobicity by introducing low surface energy substances. Therefore, most of the current super hydrophobic coating preparations are still realized by two steps, and the sample preparation efficiency is not high, and many technologies require complex equipment and conditions. Without chemical modification or realizing roughness and low surface energy synergy at the same time, it is being widely studied by scholars and is still in the development stage. Therefore, the study combined multiple methods, without using toxic reagents, by controlling the process parameters to regulate the micromorphology of the coating, and quickly prepared a superhydrophobic coating with a long-term protective effect on the alloy surface, thereby achieving good anti-corrosion effect, which is of great significance to expanding the applicability of magnesium alloys. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a highly corrosion-resistant super-hydrophobic composite coating on the surface of a magnesium alloy and a preparation method thereof. The process method is green and environmentally friendly, with a short process cycle. The obtained composite coating has excellent self-cleaning and corrosion resistance, strong bonding with the substrate, and a more lasting protective effect on the magnesium alloy.

[0005] The invention provides a highly corrosion-resistant super-hydrophobic composite coating on the surface of a magnesium alloy. The composite coating comprises an anodic oxide layer with an island structure and an electrodeposited super-hydrophobic layer formed by clusters of needle-like structures.

[0006] Furthermore, the thickness of the highly corrosion-resistant super-hydrophobic composite coating on the surface of the above-mentioned magnesium alloy is 20-80 μm.

[0007] The present invention also provides a method for preparing the above-mentioned highly corrosion-resistant super-hydrophobic composite coating on the surface of a magnesium alloy, which mainly comprises the following steps: (1) Pretreatment of magnesium alloy The magnesium alloy substrate was polished with 800#, 1000# and 2000# SiC sandpaper in sequence, and the polished samples were placed in an ultrasonic cleaner and cleaned with acetone and anhydrous ethanol respectively; (2) Anodizing The magnesium alloy after the pretreatment is used as a substrate as an anode, and an anodizing treatment is performed for 10 to 40 minutes under the condition of water bath heating. After the anodizing treatment, it is repeatedly washed with deionized water, and finally washed with anhydrous ethanol and dried for standby use, thereby obtaining a magnesium alloy substrate with an anodized layer; (3) Electrodeposition treatment The magnesium alloy substrate with an anodic oxide layer obtained in step (2) is used as a cathode, and a graphite sheet of the same size as the magnesium alloy substrate is used as an anode. The cathode and the anode are parallel to each other and separated by 2 to 20 cm. The cathode and the anode are immersed in an electrodeposition solution containing a low surface energy substance. A voltage is applied using a DC power supply. After the electrodeposition process is completed, the sample is taken out from the solution, rinsed with deionized water, and dried under atmospheric conditions.

[0008] Furthermore, in the above-mentioned method for preparing a highly corrosion-resistant super-hydrophobic composite coating on the surface of a magnesium alloy, during the anodizing process in step (2), the metal material used for the cathode is one of stainless steel, platinum, lead, and copper, and is parallel to the magnesium anode with a spacing of 2 to 20 cm.

[0009] Furthermore, in the above-mentioned method for preparing a highly corrosion-resistant super-hydrophobic composite coating on the surface of a magnesium alloy, in step (2), the water bath heating temperature is 20~70°C, and the anodizing voltage adjustment range is 5~110V; the concentrations of the components of the anodizing electrolyte used are 3~12g / L sodium oxalate, 5~25mL / L polyethylene glycol, 120~300g / L sodium hydroxide, 2~25mL / L ethylene glycol, and 2~20g / L potassium chloride, and the mass ratio of sodium oxalate to potassium chloride is 1:1.5.

[0010] Furthermore, in the above-mentioned method for preparing a highly corrosion-resistant super-hydrophobic composite coating on the surface of a magnesium alloy, in step (3), the low surface energy substance is myristic acid, the concentrations of the components of the electrodeposition solution are 9-110 g / L of anhydrous calcium chloride, 18-183 g / L of myristic acid, 2-15 mL / L of glycerol, and 8-20 g / L of potassium chloride, and the solvent is a mixed solution of ethanol and water, and the volume ratio of ethanol to water is 8.5:1.

[0011] Furthermore, in the above-mentioned method for preparing a highly corrosion-resistant super-hydrophobic composite coating on the surface of a magnesium alloy, in step (3), the voltage adjustment range is 50~120V, and the electrodeposition treatment time is 20~150min.

[0012] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a method for preparing a highly corrosion-resistant super-hydrophobic composite coating on the surface of a magnesium alloy. A magnesium hydroxide layer is prepared by an anodic oxidation method, and a super-hydrophobic coating with a multi-level micro-nano structure is prepared by an electrodeposition method on this basis. The average thickness of the obtained composite coating is 20-80 μm. A hydrogen evolution test shows that the coating significantly slows down the corrosion rate.

[0013] (2) In the composite coating structure of the present invention, the anodic oxide layer at the bottom layer provides more nucleation sites and mechanical locking force for subsequent electrodeposition. The composite coating has a strong bonding force with the substrate and is not prone to failure in a corrosive environment.

[0014] (3) The present invention is applicable to different types of magnesium alloys, has simple process equipment, and does not use toxic substances, thus meeting the requirements of environmentally friendly development. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The surface morphology of the composite coating prepared in Example 1 of the present invention; Figure 2 This is the contact angle of the composite coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0016] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0017] In the following embodiments of the present invention, the method for preparing a highly corrosion-resistant super-hydrophobic composite coating on the surface of a magnesium alloy comprises the following steps: (1) Pretreatment of magnesium alloy The magnesium alloy substrate was polished with 800#, 1000# and 2000# SiC sandpaper in sequence, and the polished samples were placed in an ultrasonic cleaner and cleaned with acetone and anhydrous ethanol respectively; (2) Anodizing The magnesium alloy substrate after the pretreatment is used as an anode, and an anodizing treatment is performed for 10 to 40 minutes under the condition of water bath heating. After the anodizing treatment, it is repeatedly washed with deionized water, and finally washed with anhydrous ethanol and dried for standby use, thereby obtaining a magnesium alloy substrate with an anodized layer; (3) Electrodeposition treatment The magnesium alloy substrate with an anodic oxide layer obtained in step (2) is used as a cathode, and a graphite sheet of the same size as the magnesium alloy substrate is used as an anode. The cathode and the anode are parallel to each other and separated by 2 to 20 cm. The cathode and the anode are immersed in an electrodeposition solution containing a low surface energy substance. A voltage is applied using a DC power supply. After the electrodeposition process is completed, the sample is taken out from the solution, rinsed with deionized water, and dried under atmospheric conditions. Example 1

[0018] Material: LA103Z magnesium alloy The pre-treated LA103Z magnesium alloy was used as the anode and 316 stainless steel was used as the cathode. The two were parallel to each other and 2 cm apart. They were heated in a water bath at 40°C and the anodic oxidation voltage was 5 V for 10 minutes. The electrolyte composition for anodic oxidation was 3g / L sodium oxalate, 5mL / L polyethylene glycol, 120g / L sodium hydroxide, 3mL / L ethylene glycol, and 4.5g / L potassium chloride. After anodizing, the magnesium alloy sample was repeatedly washed with deionized water, and finally washed with anhydrous ethanol and dried. The sample with an anodized layer was used as the cathode, and a graphite sheet of the same size was used as the anode. The two were parallel to each other and 2 cm apart. They were vertically immersed in an electrodeposition solution containing 9 g / L anhydrous calcium chloride, 18 g / L tetradecanoic acid, 2 mL / L glycerol, and 8 g / L potassium chloride. The solvent was a mixed solution of ethanol and water, and the volume ratio of ethanol to water was 8.5:1. A DC power supply was used to apply a constant voltage of 50 V. The electrodeposition treatment was performed for 20 minutes. After the electrodeposition process was completed, the sample was taken out from the solution, rinsed with deionized water, and dried under atmospheric conditions.

[0019] The prepared composite coating has a thickness of 35 μm, a surface contact angle of 155.2°, and the adhesion between the coating and the substrate reaches ISO grade 0 of GB / T 4893.4-2013. For long-term corrosion resistance, the hydrogen evolution test shows that the annual corrosion rate of the composite coating is as low as 0.13 mm·y -1 .

[0020] The composite coating prepared in Example 1 was subjected to SEM test, and the surface morphology was as follows: Figure 1 As shown in Figure 2, the super-hydrophobic surface is composed of clusters of needle-like structures. The multi-level micro-nanostructure can retain a large amount of air to "lift" the droplets. The state of the droplets on the surface of the composite coating is shown in Figure 2. Figure 2As shown, the composite coating has obvious hydrophobicity, and the droplets are not easy to penetrate and spread on the coating surface, presenting a spherical shape. Example 2

[0021] Material: AZ31 magnesium alloy The pre-treated AZ31 magnesium alloy was used as the anode and the pure copper sheet was used as the cathode. The two were parallel to each other and the distance between them was 7 cm. They were heated in a water bath at 50°C and the anodic oxidation voltage was 20 V for 20 minutes. The electrolyte composition for anodic oxidation was 6g / L sodium oxalate, 7mL / L polyethylene glycol, 150g / L sodium hydroxide, 6mL / L ethylene glycol, and 9g / L potassium chloride. After anodizing, the magnesium alloy sample was repeatedly washed with deionized water and finally washed with anhydrous ethanol and dried. The sample with an anodized layer was used as the cathode and a graphite sheet of the same size was used as the anode. The two were parallel to each other and 5 cm apart. They were vertically immersed in an electrodeposition solution containing 15 g / L anhydrous calcium chloride, 27 g / L tetradecanoic acid, 6 mL / L glycerol, and 11 g / L potassium chloride. The solvent was a mixed solution of ethanol and water with a volume ratio of ethanol to water of 8.5:1. A DC power supply was used to apply a constant voltage of 70 V. The electrodeposition treatment was performed for 30 minutes. After the electrodeposition process was completed, the sample was taken out of the solution, rinsed with deionized water, and dried under atmospheric conditions.

[0022] The prepared composite coating has a thickness of 47 μm, a surface contact angle of 157.3°, and the adhesion between the coating and the substrate reaches ISO grade 0 of GB / T 4893.4-2013. For long-term corrosion resistance, the hydrogen evolution test shows that the annual corrosion rate of the composite coating is as low as 0.08 mm·y -1 . Example 3

[0023] Material: AZ91 magnesium alloy The pre-treated AZ91 magnesium alloy was used as the anode and the pure copper sheet was used as the cathode. The two were parallel to each other and the distance between them was 10 cm. They were heated in a water bath at 60°C and the anodic oxidation voltage was 70 V for 35 minutes. The electrolyte composition for anodic oxidation was 8g / L sodium oxalate, 7mL / L polyethylene glycol, 150g / L sodium hydroxide, 6mL / L ethylene glycol, and 12g / L potassium chloride. After anodizing, the magnesium alloy sample was repeatedly washed with deionized water and finally washed with anhydrous ethanol and dried. The sample with an anodized layer was used as the cathode and a graphite sheet of the same size was used as the anode. The two were parallel to each other and 7 cm apart. They were vertically immersed in an electrodeposition solution containing 30 g / L anhydrous calcium chloride, 52 g / L tetradecanoic acid, 6 mL / L glycerol, and 9 g / L potassium chloride. The solvent was a mixed solution of ethanol and water with a volume ratio of ethanol to water of 8.5:1. A DC power supply was used to apply a constant voltage of 80 V. The electrodeposition treatment lasted for 45 minutes. After the electrodeposition process was completed, the sample was removed from the solution, rinsed with deionized water, and dried under atmospheric conditions.

[0024] The prepared composite coating has a thickness of 56 μm, a surface contact angle of 160.3°, and the adhesion between the coating and the substrate reaches ISO grade 0 of GB / T 4893.4-2013. For long-term corrosion resistance, the hydrogen evolution test shows that the annual corrosion rate of the composite coating is as low as 0.04 mm·y -1 . Example 4

[0025] Material: AM60 magnesium alloy The pre-treated AM60 magnesium alloy was used as the anode and the platinum sheet was used as the cathode. The two were parallel to each other and the distance between them was 12 cm. They were heated in a water bath at 55°C and the anodic oxidation voltage was 85 V for 40 minutes. The electrolyte composition for anodic oxidation was 10 g / L sodium oxalate, 7 mL / L polyethylene glycol, 150 g / L sodium hydroxide, 6 mL / L ethylene glycol, and 15 g / L potassium chloride. After anodizing, the magnesium alloy sample was repeatedly washed with deionized water and finally washed with anhydrous ethanol and dried. The sample with an anodized layer was used as the cathode and a graphite sheet of the same size was used as the anode. The two were parallel to each other and 12 cm apart. They were vertically immersed in an electrodeposition solution containing 35 g / L anhydrous calcium chloride, 60 g / L tetradecanoic acid, 9 mL / L glycerol, and 12 g / L potassium chloride. The solvent was a mixed solution of ethanol and water with a volume ratio of ethanol to water of 8.5:1. A DC power supply was used to apply a constant voltage of 100 V. The electrodeposition treatment was performed for 60 minutes. After the electrodeposition process was completed, the sample was taken out of the solution, rinsed with deionized water, and dried under atmospheric conditions.

[0026] The prepared composite coating has a thickness of 60 μm, a surface contact angle of 160.8°, and the adhesion between the coating and the substrate reaches ISO grade 0 of GB / T 4893.4-2013. For long-term corrosion resistance, the hydrogen evolution test shows that the annual corrosion rate of the composite coating is as low as 0.07 mm·y -1 . Example 5

[0027] Material: ZK61 magnesium alloy The pre-treated ZK61 magnesium alloy was used as the anode and the platinum sheet was used as the cathode. The two were parallel to each other and the distance between them was 18 cm. They were heated in a water bath at 60°C and the anodic oxidation voltage was 95 V for 40 minutes. The electrolyte composition for anodic oxidation was 12 g / L sodium oxalate, 12 mL / L polyethylene glycol, 120 g / L sodium hydroxide, 10 mL / L ethylene glycol, and 18 g / L potassium chloride. After anodizing, the magnesium alloy sample was repeatedly washed with deionized water and finally washed with anhydrous ethanol and dried. The sample with an anodized layer was used as the cathode and a graphite sheet of the same size was used as the anode. The two were parallel to each other and 16 cm apart. They were vertically immersed in an electrodeposition solution containing 80 g / L anhydrous calcium chloride, 96 g / L tetradecanoic acid, 10 mL / L glycerol, and 12 g / L potassium chloride. The solvent was a mixed solution of ethanol and water with a volume ratio of ethanol to water of 8.5:1. A DC power supply was used to apply a constant voltage of 100 V. The electrodeposition treatment lasted for 90 minutes. After the electrodeposition process was completed, the sample was taken out of the solution, rinsed with deionized water, and dried under atmospheric conditions.

[0028] The thickness of the prepared composite coating is 72 μm, the contact angle of the composite coating surface is 162.8°, and the adhesion between the coating and the substrate reaches ISO grade 0 of GB / T 4893.4-2013. For long-term corrosion resistance, the hydrogen evolution test shows that the annual corrosion rate of the composite coating is as low as 0.05 mm·y -1 .

Claims

1. A highly corrosion-resistant super-hydrophobic composite coating on the surface of a magnesium alloy, characterized in that: The composite coating comprises an anodic oxide layer with an island structure prepared on the surface of a magnesium alloy substrate by using an anodic oxide technology and a super hydrophobic layer formed by needle-like structure clusters prepared on the surface of the anodic oxide layer by using an electrodeposition technology.

2. A highly corrosion-resistant super-hydrophobic composite coating on a magnesium alloy surface according to claim 1, characterized in that: The composite coating has a thickness of 20-80 μm.

3. The method for preparing a highly corrosion-resistant super-hydrophobic composite coating on a magnesium alloy surface according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Pretreatment of magnesium alloy The magnesium alloy substrate was polished with 800#, 1000# and 2000# SiC sandpaper in sequence, and the polished samples were placed in an ultrasonic cleaner and cleaned with acetone and anhydrous ethanol respectively; (2) Anodizing The treated magnesium alloy substrate obtained in step (1) is used as an anode, and anodized for 10 to 40 minutes under a water bath heating condition. After the anodization treatment, it is repeatedly washed with deionized water, and finally washed with anhydrous ethanol and dried for standby use to obtain a magnesium alloy substrate with an anodized layer; (3) Electrodeposition treatment The magnesium alloy substrate with an anodic oxide layer obtained in step (2) is used as a cathode, and a graphite sheet of the same size as the magnesium alloy substrate is used as an anode. The cathode and the anode are parallel to each other and separated by 2 to 20 cm. The cathode and the anode are immersed in an electrodeposition solution containing a low surface energy substance. A voltage is applied using a DC power supply. After the electrodeposition process is completed, the sample is taken out from the solution, rinsed with deionized water, and dried under atmospheric conditions.

4. The method for preparing a highly corrosion-resistant super-hydrophobic composite coating on a magnesium alloy surface according to claim 3, characterized in that: In step (2), the metal material used for the cathode is one of stainless steel, platinum, lead and copper, and is parallel to the magnesium anode with a spacing of 2 to 20 cm.

5. The method for preparing a highly corrosion-resistant super-hydrophobic composite coating on a magnesium alloy surface according to claim 3, characterized in that: In step (2), the water bath heating temperature is 20-70° C., the anodizing voltage adjustment range is 5-110 V; the concentrations of the components of the anodizing electrolyte used are: 3-12 g / L sodium oxalate, 5-25 mL / L polyethylene glycol, 120-300 g / L sodium hydroxide, 2-25 mL / L ethylene glycol, 2-20 g / L potassium chloride, and the mass ratio of sodium oxalate to potassium chloride is 1:1.

5.

6. The method for preparing a highly corrosion-resistant super-hydrophobic composite coating on a magnesium alloy surface according to claim 3, characterized in that: In step (3), the low surface energy substance is myristic acid, the concentrations of the components of the electrodeposition solution are 9-110 g / L anhydrous calcium chloride, 18-183 g / L myristic acid, 2-15 mL / L glycerol, and 8-20 g / L potassium chloride, and the solvent is a mixed solution of ethanol and water, with a volume ratio of ethanol to water of 8.5:

1.

7. The method for preparing a highly corrosion-resistant super-hydrophobic composite coating on a magnesium alloy surface according to claim 3, characterized in that: In step (3), the voltage adjustment range is 50-120 V, and the electrodeposition treatment time is 20-150 min.

Citation Information

Patent Citations

  • Methods for preparing super-hydrophobic coatings on surfaces of magnesium and magnesium alloy

    CN103088380A

  • Magnesium alloy surface treatment method and treated magnesium alloy

    CN113774462A

  • Method for preparing super-hydrophobic composite film layer on surface of magnesium alloy

    CN118127596A